Advertisement Remove all ads

Obtain the differential equation by eliminating the arbitrary constants from the following equation: (y - a)2 = 4(x - b) - Mathematics and Statistics

Sum

Obtain the differential equation by eliminating the arbitrary constants from the following equation:

(y - a)2 = 4(x - b)

Advertisement Remove all ads

Solution

(y - a)2 = 4(x - b)

Differentiating twice w.r.t. x, we get

`2 ("y - a")*"d"/"dx"("y - a") = 4 "d"/"dx" ("x - b")`

∴ `2 ("y - a")*("dy"/"dx" - 0) = 4(1 - 0)`

∴ `2 ("y - a")"dy"/"dx" = 4`

∴ `("y - a")"dy"/"dx" = 2`     ....(1)

Differentiating again w.r.t. x, we get

`("y - a")"d"/"dx" ("dy"/"dx") + "dy"/"dx"*"d"/"dx" ("y - a") = 0`

∴ `("y - a")("d"^2"y")/"dx"^2 + "dy"/"dx" * ("dy"/"dx" - 0) = 0`

∴ `("y - a")("d"^2"y")/"dx"^2 + ("dy"/"dx")^2 = 0`

∴ `2/("dy"/"dx") * ("d"^2"y")/"dx"^2 + ("dy"/"dx")^2 = 0`      .....[By (1)]

∴ `2 ("d"^2"y")/"dx"^2 + ("dy"/"dx")^3 = 0`

This is the required D.E.

Concept: Formation of Differential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×